2015
DOI: 10.1038/nplants.2015.80
|View full text |Cite
|
Sign up to set email alerts
|

Grassland productivity limited by multiple nutrients

Abstract: Terrestrial ecosystem productivity is widely accepted to be nutrient limited(1). Although nitrogen (N) is deemed a key determinant of aboveground net primary production (ANPP)(2,3), the prevalence of co-limitation by N and phosphorus (P) is increasingly recognized(4-8). However, the extent to which terrestrial productivity is co-limited by nutrients other than N and P has remained unclear. Here, we report results from a standardized factorial nutrient addition experiment, in which we added N, P and potassium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
455
5
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 469 publications
(496 citation statements)
references
References 31 publications
31
455
5
5
Order By: Relevance
“…Other low nutrient grasslands have shown a degree of NP co-limitation, with significantly greater above-ground biomass in NP treatments than in the control or with addition of N or P separately (Willems et al, 1993;Carroll et al, 2003). Across grasslands globally NP colimitation is widespread (Elser et al, 2007;Bracken et al, 2015;Fay et al, 2015). By contrast, in a Dutch study, N addition was reported to increase plant biomass in diverse chalk grassland, overriding any subtle P effects (Bobbink 1991), therefore not all calcareous grasslands are necessarily P limited.…”
Section: Impact Of N Additionmentioning
confidence: 69%
“…Other low nutrient grasslands have shown a degree of NP co-limitation, with significantly greater above-ground biomass in NP treatments than in the control or with addition of N or P separately (Willems et al, 1993;Carroll et al, 2003). Across grasslands globally NP colimitation is widespread (Elser et al, 2007;Bracken et al, 2015;Fay et al, 2015). By contrast, in a Dutch study, N addition was reported to increase plant biomass in diverse chalk grassland, overriding any subtle P effects (Bobbink 1991), therefore not all calcareous grasslands are necessarily P limited.…”
Section: Impact Of N Additionmentioning
confidence: 69%
“…The Güsewell (2004) range for co-NP limitation 307 is broader than some ranges proposed by others (e.g., Koerselman and Meuleman 1996). 308 more common than previously thought (Fay et al 2015). This suggests that past narrow N: 310 P ratio ranges may have mistakenly predicted single nutrient limitation in some 311 communities that were co-limited.…”
Section: Discussion 253mentioning
confidence: 43%
“…LAI represents the 1-sided leaf surface area available 69 for photosynthesis, and variability in this metric strongly influences key ecosystem 70 functions such as productivity and transpiration (Street et al 2012 occurs. This may also apply to LAI-TFP (total foliar phosphorus) relationships in P-limited 95 or co-NP limited systems found in many grasslands (Fay et al 2015). Furthermore, in 96 herbaceous plant communities where the canopy makes up the majority of above ground 97 biomass, such relationships may allow estimates of aboveground stocks of N and P from 98 measurements of LAI, further providing data needed for process-based modelling.…”
Section: Introduction 34mentioning
confidence: 99%
See 2 more Smart Citations